Spatial Variation in Primary Production in the Eastern Indian Ocean - Liu, Haijiao; Song, Yuyao; Zhang, Xiaodong; Zhang, Guicheng; Wu, Chao; Wang, Xingzhou; Thangaraj, Satheeswaran; Wang, Dongxiao; Chen, Ju; Sun, Jun (Frontiers in Marine Science, 2021)
Using the deck-incubation 14C tracer technique, phytoplankton primary production measurements were conducted in the eastern Indian Ocean (EIO) from February 27 to April 22, 2017. The estimated daily carbon production rates integrated over the photic zone ranged from 113 to 817 mgC m-2 d-1, with a mean of 522 mgC m-2 d-1. The mixed layer integrated primary production (MLD-PP) ranged from 29.0 to 303.7 mgC m-2 d-1 (mean 177.2 mgC m-2 d-1). And the contribution of MLD-PP to the photic zone integrated PP varied between 19% and 51% (mean 36%). Spatial variability of hydrochemistry, phytoplankton groups, and productivity were found among the study region, while with no distinct significance. Surface primary production rates were relatively higher in the northern area near river discharge and lower in the equatorial Indian Ocean due to the presence of the inter-monsoonal Wyrtki jets which was characterized by depressed thermocline and nitracline. The photic zone integrated primary production exhibited linear (positively) relation with nutrients, but with no significance, indicating partial control of macro-nutrients and light limitation on carbon fixation. As evident from vertical profiles, primary production mainly happened above the nitracline depth as well as high photosynthetic efficiency. Phytoplankton (>5μm) including dinoflagellates, Trichodesmium, and coccolithophores and dissolved nutrients were thought to be correlated with primary production during the study period. The measured on-deck biological data in our study allows for a general understanding of the trends in primary productivity in the survey area of EIO, as well as can be incorporated into global primary production models.